Soluble Mediators Regulating Immunity in Early Life - Pettengill, Matthew Aaron; van Haren, Simon Daniël; Levy, Ofer (Frontiers in Immunology, 2014)
Soluble factors in blood plasma have a substantial impact on both the innate and adaptive immune responses. The complement system, antibodies, and anti-microbial proteins and peptides can directly interact with potential pathogens, protecting against systemic infection. Levels of these innate effector proteins are generally lower in neonatal circulation at term delivery than in adults, and lower still at preterm delivery. The extracellular environment also has a critical influence on immune cell maturation, activation, and effector functions, and many of the factors in plasma, including hormones, vitamins, and purines, have been shown to influence these processes for leukocytes of both the innate and adaptive immune systems. The ontogeny of plasma factors can be viewed in the context of a lower effectiveness of immune responses to infection and immunization in early life, which may be influenced by the striking neonatal deficiency of complement system proteins or enhanced neonatal production of the anti-inflammatory cytokine IL-10, among other ontogenic differences. Accordingly, we survey here a number of soluble mediators in plasma for which age-dependent differences in abundance may influence the ontogeny of immune function, particularly direct innate interaction and skewing of adaptive lymphocyte activity in response to infectious microorganisms and adjuvanted vaccines.